(untitled) (International Seven Journal of Multidisciplinary, 2023)
The article explores the intricate relationship between top predator tourism, conservation and socio-economic considerations. Starting with the innate fascination that top predators offer, the article delves into their ecological significance and their representation in cultural narratives. Through a dual methodological approach involving systematic review and secondary data analysis, specific case studies from Africa, the United States, Brazil and India were dissected. These detailed analyses identified the nuances of human-animal interactions, security concerns, economic implications and conservation challenges unique to each region. The comparative analysis revealed common patterns of human-animal conflict, tourism’s economic contributions and ethical considerations. An emphasis on community engagement, safety protocols, habitat preservation and sustainable tourism practices was evident in the recommendations. The study concludes with a call for a harmonious blend of tourism aspirations and conservation imperatives, especially amid global challenges such as climate change. Top predator tourism, when carried out ethically and sustainably, presents an invaluable opportunity for both ecological preservation and economic growth.